Combinations of Ghd7, Ghd8, and Hd1 determine strong heterosis of commercial rice hybrids in diverse ecological regions. (10th July 2021) - Zhou, Xiangchun; Nong, Chunxiao; Wu, Bi; Zhou, Tianhao; Zhang, Bo; Liu, Xingshao; Gao, Guanjun; Mi, Jiaming; Zhang, Qinglu; Liu, Haiyang; Liu, Shisheng; Li, Zhixin; et al.
Abstract : Combinations of the major flowering genes Ghd7, Ghd8, and Hd1 largely determine the regional adaptation and heterosis of hybrid rice, and gene diagnosis is helpful in breeding for heading date. Abstract: Heterosis of grain yield is closely associated with heading date in crops. Gene combinations of the major heading date genes Ghd7, Ghd8, and Hd1 play important roles in enhancing grain yield and adaptation to ecological regions in rice. However, the predominant three-gene combinations for a specific ecological region remain unclear in both three-line and two-line hybrids. In this study, we sequenced these three genes of 50 cytoplasmic male sterile/maintainer lines, 31 photo-thermo-sensitive genic male sterile lines, and 109 restorer lines. Sequence analysis showed that hybrids carrying strong functional alleles of Ghd7 and Hd1 and non-functional Ghd8 are predominant in three-line hybrids and are recommended for rice production in the subtropics around 30°N/S. Hybrids carrying strong functional Ghd7 and Ghd8 and non-functional Hd1 are predominant in two-line hybrids and are recommended for low latitude areas around 23.5°N/S rich in photothermal resources. Hybrids carrying strong functional Ghd7 and Ghd8 and functional Hd1 were not identified in commercial hybrids in the middle and lower reaches of the Yangtze River, but they have high yield potential in tropical regions because they have the strongest photoperiod sensitivity. Based on these findings, two genic sterile lines, Xiangling 628S and C815S, whose hybrids often head very late, were diagnosed with these three genes, and Hd1 was targeted to be knocked out in Xiangling 628S and replaced with hd1 in C815S. The hybrids developed from both modified sterile lines in turn had appropriate heading dates and significantly improved grain yield. This study provides new insights for breeding design to develop hybrids for various regions.